Improving the corporate HRDD: Human rights risk identification in global supply chains - Niemi, Susanna (2025)
Human rights are central to ethical business conduct. Respecting human rights is mandated in various ways through legislation, international standards, and stakeholder expectations. Standards such as the United Nations Guiding Principles on Business and Human Rights (UNGPs) provide a framework for respecting human rights. However, pragmatic guidance and translating requirements into everyday business practices are lacking.